1997
DOI: 10.1123/jsep.19.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Does Aerobic Exercise Decrease Brain Activation?

Abstract: In the present study, participants were randomly assigned to an exercise or a nonexercise group to measure brain activation (spontaneous EEG activity), affect, and cognitive functioning before and after a 15-min treatment period. Exercisers (a) sat quietly for 5 min, (b) exercised for 15 min, (c) recovered for 5 min, and (d) completed a 15-min vigilance task. Nonexercisers did not exercise. There was a significant (a) Condition × Band × Time interaction for EEG activity, (b) Condition × Time interaction for Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 0 publications
0
43
2
2
Order By: Relevance
“…In addition, reductions in resting state activation were found in the subgenual prefrontal cortex after a 90-min walk in nature as compared with a 90-min walk in an urban environment [3]. Electroencephalography (EEG) has shown that observing static rural images can induce increases in alpha (8)(9)(10)(11)(12)(13) Hz) neural activity [14,15] associated with relaxation [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reductions in resting state activation were found in the subgenual prefrontal cortex after a 90-min walk in nature as compared with a 90-min walk in an urban environment [3]. Electroencephalography (EEG) has shown that observing static rural images can induce increases in alpha (8)(9)(10)(11)(12)(13) Hz) neural activity [14,15] associated with relaxation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is associated with a-enhancement, particularly in the frontal cortex (e.g., Kubitz & Pothakos, 1997). The increase in a-activity during and after exercise has been interpreted in the literature as indicative of decreased brain activation (Kubitz & Pothakos, 1997).…”
Section: Endurance Runningmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] parametric paired t-test maps comparing the averaged spectral power across subjects over time (x-axes) and frequency (y-axes) during moderate-to-high intensity and light intensity exercise in standard trials. The enclosed areas denote significant clusters of channels and time with p < 0.025.…”
Section: Cc-by-nc-nd 40 International Licensementioning
confidence: 99%
“…This is probably the main reason why only a reduced number of studies have investigated brain activity during exercise, primarily using electroencephalography (EEG). The majority of these studies focused on changes in the alpha frequency band at frontal localizations [9] reporting increased alpha activity during exercise [10] [11]. The only meta-analysis to date [12], however, indicates that alpha brain rhythm activation is not selective and maybe parallel by an increase of other brain rhythms, suggesting a possible power increase across the entire frequency spectrum during exercise.…”
Section: Introductionmentioning
confidence: 99%